2009
DOI: 10.1007/s10495-009-0380-4
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous HIV-1 Vpr-mediated apoptosis and proteome alteration of human T-cell leukemia virus-1 transformed C8166 cells

Abstract: HIV-1 viral protein R (Vpr) can induce cell cycle arrest and cell death, and may be beneficial in cancer therapy to suppress malignantly proliferative cell types, such as adult T-cell leukemia (ATL) cells. In this study we examined the feasibility of employing the HIV-vpr gene, via targeted gene transfer, as a potential new therapy to kill ATL cells. We infected C8166 cells with a recombinant adenovirus carrying both vpr and GFP genes (rAd-vpr), as well as the vector control virus (rAd-vector). G2/M phase cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…In animals, Ross et al reported that PHBs were upregulated upon the activation of primary human T cells (40). PHB1 also increases when challenged with viruses in human cell lines (41,42). In our study, PcPHB1 was universally expressed in several tissues (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…In animals, Ross et al reported that PHBs were upregulated upon the activation of primary human T cells (40). PHB1 also increases when challenged with viruses in human cell lines (41,42). In our study, PcPHB1 was universally expressed in several tissues (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Previous reports of PHB expression during HIV infection are mixed. PHB appears to be over-expressed when cells were exposed to HIV envelope protein (Molina et al, 2007), but Vpr expression reduces PHB levels (He et al, 2009). Recently PHB was found to interact directly with HIV-1 envelope protein (Emerson et al, 2010; Jager et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Two major apoptotic pathways exploited by cells were discovered as an extrinsic or intrinsic pathway (31) by apical activation of caspase-8 or caspase-9, respectively. Early observations in various cell types showed that Vpr induced apoptosis either via the extrinsic pathway or intrinsic pathway (32)(33)(34)(35). Cell type-specific variations and context may account for these discrepancies (36).…”
Section: Discussionmentioning
confidence: 99%